Piper nigrum allelopathy on the germination and initial growth of Lactuca sativa and Panicum maximum - Rodrigues Filho, Josinei; Follador Nogueira, Enes; França, Hildegardo; Borges Corte, Viviana; Tereza de Almeida Leite Perin , Idalina; Henrique Waichert, Rodolpho (Comunicata Scientiae, 2023)
The increased demand for food promotes greater use of agricultural inputs and pesticides used in pest control. Many of these products have negative environmental and public health impacts. Thus, there is a need for alternative products, with allelopathic capacity that reduce such impacts. The objective of this work was to verify the allelopathic potential of Piper nigrum L. extracts on the germination and initial growth of Panicum maximum Jacq. and Lactuca sativa seeds. The experimental design used was completely randomized, using two plant organs (leaf and seed), three extractors (hexane, ethyl acetate and methanol) and five concentrations (0 mg/L, 200 mg/L, 400 mg/L, 600 mg/L and 800 mg/L). It was verified the influence of these extracts on germination speed index (IVG), germination percentage (G), mean germination time (TMG), allelopathy index (IA), shoot growth (CPA) and in the root growth (CR) of seeds and seedlings. The leaf and seed extracts, at all concentrations and extractors tested, did not show phytotoxicity or had a very small inhibitory effect on germination and initial growth of Lactuca sativa. For Panicum maximum, ethyl acetate and methanol seed extracts, at the highest concentrations tested, had the most significant negative effects on the weed. Thus, it was possible to infer that extracts from Piper nigrum seeds have potential use in the control of the weed Panicum maximum.